Debunking highly prevalent health misinformation using audio dramas delivered by WhatsApp: evidence from a randomised controlled trial in Sierra Leone. Issue 11 (10th November 2021) - Winters, Maike; Oppenheim, Ben; Sengeh, Paul; Jalloh, Mohammad B; Webber, Nance; Pratt, Samuel Abu; Leigh, Bailah; Molsted-Alvesson, Helle; Zeebari, Zangin; Sundberg, Carl Johan; Jalloh, Mohamed F; Nordenstedt, Helena
Abstract : Introduction: Infectious disease misinformation is widespread and poses challenges to disease control. There is limited evidence on how to effectively counter health misinformation in a community setting, particularly in low-income regions, and unsettled scientific debate about whether misinformation should be directly discussed and debunked, or implicitly countered by providing scientifically correct information. Methods: The Contagious Misinformation Trial developed and tested interventions designed to counter highly prevalent infectious disease misinformation in Sierra Leone, namely the beliefs that (1) mosquitoes cause typhoid and (2) typhoid co-occurs with malaria. The information intervention for group A (n=246) explicitly discussed misinformation and explained why it was incorrect and then provided the scientifically correct information. The intervention for group B (n=245) only focused on providing correct information, without directly discussing related misinformation. Both interventions were delivered via audio dramas on WhatsApp that incorporated local cultural understandings of typhoid. Participants were randomised 1:1:1 to the intervention groups or the control group (n=245), who received two episodes about breast feeding. Results: At baseline 51% believed that typhoid is caused by mosquitoes and 59% believed that typhoid and malaria always co-occur. The endline survey was completed by 91% of participants. Results from the intention-to-treat, per-protocol and as-treated analyses show that both interventions substantially reduced belief in misinformation compared with the control group. Estimates from these analyses, as well as an exploratory dose–response analysis, suggest that direct debunking may be more effective at countering misinformation. Both interventions improved people's knowledge and self-reported behaviour around typhoid risk reduction, and yielded self-reported increases in an important preventive method, drinking treated water. Conclusion: These results from a field experiment in a community setting show that highly prevalent health misinformation can be countered, and that direct, detailed debunking may be most effective. Trial registration number: NCT04112680 .